The evolution of morphology - Carstairs-McCarthy, Andrew, 1945- (Oxford ; New York : Oxford University Press, 2010)
This book considers the evolution of the grammatical structure of words in the more general contexts of human evolution and the origins of language. The consensus in many fields is that language is well designed for its purpose, and became so either through natural selection or by virtue of non-biological constraints on how language must be structured. Andrew Carstairs-McCarthy argues that in certain crucial respects language is not optimally designed. This can be seen, he suggests, in the existence of not one but two kinds of grammatical organization - syntax and morphology - and in the morpho.
Preface and acknowledgements; 1 Design in language and design in biology; 2 Why there is morphology: Traditional accounts; 3 A cognitive-articulatory dilemma; 4 Modes of synonymy avoidance; 5 The ancestors of affixes; 6 The ancestors of stem alternants; 7 Derivation, compounding, and lexical storage; 8 Morphological homonymy and morphological meanings; 9 Conclusions; References; Language Index; Name Index; Subject Index.
Includes bibliographical references and index.
Print version record.
Keywords: Grammar, Comparative and general -- Morphosyntax; Historical linguistics; LANGUAGE ARTS & DISCIPLINES -- Linguistics -- Morphology; Grammar, Comparative and general -- Morphosyntax; Historical linguistics; Electronic books; Electronic books